Fundamental Approaches to Software Engineering: 28th International Conference, FASE 2025, Held as Part of the International Joint Conferences on Theory and Practice of Software, ETAPS 2025, Hamilton, ON, Canada, May 3–8, 2025, Proceedings (Lecture Notes in Computer Science, 2025)
This open access book constitutes the proceedings of the 28th International Conference on Fundamental Approaches to Software Engineering, FASE 2025, which was held as part of the International Joint Conferences on Theory and Practice of Software, ETAPS 2025, in Hamilton, Canada, in May 2025. The 9 full and 2 short papers included in the proceedings, together with one invited keynote paper and 3 tool competition papers, were carefully reviewed and selected from 31 submissions. They deal with up to date research in software engineering and its applications in, e.g., quality and testing foundations for AI-based systems, requirements engineering, etc.